Pengaruh Motivasi dan Lingkungan Kerja Non-Fisik Terhadap Kinerja Karyawan PT. Bank KB Bukopin Tbk. Kantor Pusat Selama Masa Pandemi Covid-19 - Rezqi Ananda Basid; Kevin Gian Heriza (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine the effect of motivation and non-physical work environment on employee performance. The object of this research is the employees of PT. Bank KB Bukopin Tbk. Head Office in accordance with the criteria that have been made by the author. Data was obtained through the deployment of the questionnaire to 200 samples for employees and 46 samples for employees. The analytical method used in this study is the validity test, reliability test, classical assumption test, and hypothesis testing. The results obtained in this study conclude that motivation has a positive effect on employee performance with a value of 2,725 and the non-physical work environment has a negative effect on employee performance with a value of -3,767. Results obtained by researchers in the simultaneous test of the motivation variables and non-physical work environment have a significant value of 0.001 and 0.002. This shows that the motivation variable and non-physical work environment simultaneously affect the performance variables of the employee